Star Power and Risk. A Political Economic Study of Casting Trends in Hollywood - James McMahon (Capital as Power - Toward a New Cosmology of Capitalism, 2022)
This paper builds an empirical and theoretical model to analyze how the financial goal of risk reduction changed the insides of Hollywood's star system. For the moviegoer looking at Hollywood cinema from the outside, the function of the star system has remained the same since the 1920s: to have recognizable actors attract large audiences to Hollywood's biggest and most expensive productions. The composition of this system is, however, sensitive to many historical changes in the business and culture of cinema. If the evolution of Hollywood's star system is shaped by broader social factors, risk reduction would be a key factor after 1980. This paper uses Internet Movie Database (IMDb) casting data to analyze how the star system was a factor in this period of risk reduction. Film casting assists risk reduction when a star system is built on controlled repetition. Repetitive casting - choosing the same people to star in a series of films - is a form of control because repetitive selection is the inequality of opportunity by another name: if an in-group is internally repetitive when alternatives exist, an out-group is repeatedly excluded. There are two key conclusions to the analysis of the IMDb dataset. First, casting repetitiveness/inequality in the blockbuster era of Hollywood (1980-present) is low compared to Hollywood's "classical" studio system (1930-1948). Second, the historically low repetitiveness/inequality can be misleading if we ignore sector characteristics such as firm size and level of theatrical distribution. Within the top-tier, whether measured by size of distributor or number of opening theatres in theatrical release, Hollywood relies on repetitive casting. The theoretical part of this paper will identify the role of capitalist power in the formation of a star system. Capitalist power, in this case, is defined as the ability of Hollywood to control everything from the industrial production of films to the broader social relations of cinema. This control is never absolute, but the role of capitalist power in the star system has a key purpose: to make sure that casting decisions are complementary to business interests.
Keywords: P16; Z1; 330; culture; Hollywood; inequality; risk